Clinical Study for Oxidative Stress and Lipid Profile Levels in Patients with Cardiac Arrhythmias - Mohammed. L. A. Al-Baaj (Journal of Global Pharma Technology, 2016)
Cardiac arrhythmia is a disturbance heart rhythm. Most types of arrhythmia are not serious, while there are some that types can be life threatening promptly because it impacts the pumping action of the heart substantially, enough to disrupt blood supply to the body, potentially leading to sudden cardiac death. The present study is designed to determine the levels of (MDA) (malondialdehyde) as a marker for lipid peroxidation , in addition, measurement the level of lipid profile (cholesterol TCH, triglyceride TG, high density lipoprotein HDL, low density lipoprotein LDL, very low density lipoprotein vLDL, in patients of cardiac arrhythmia. The study includes (110) subjects with average age (62.0±3.0) years and the average of BMI was (27.80 ± 3.0 kg/m2) which were divided into five groups: (20) patients of (AF), (17) Patients of (SVT), (20) patients of (VT), (18) patients of (PVCs) and (35) clinically healthy subjects, who were attend blood bank to blood donation as control groups. The study aims to shed a light on the correlation between oxidants and lipid profile in patients with cardiac arrhythmia .The results show that there were a significant increases in serum concentrations of each of (MDA) ,(TCH), (TG), (LDL) and (vLDL) in all of patients groups in comparison with control group (P≤0.05), as for level of (HDL) there was a significant reduction (P≤0.05) In patients of AF in comparison with each one of study groups, also there was a significant increase in concentrations of MDA of patients of VT compared with each of AF, SVT, PVCs (P≤0.05) and non-significant increase in serum concentrations of MDA between SVT and AF ,while there was slightly significant increase between each of AF and SVT compared with PVCs(P≤0.05). On the other hand Pearson’s correlation coefficient analysis showed a positive correlation between MDA level and each lipid profile parameter, except HDL which showed a negative correlation in all groups of cardiac arrhythmia.Key words: Arrhythmia, AF, SVT, PVCs, VT, Oxidative stress and MDA.